Komunikasi Pembangunan dan Kemandirian Desa (Studi Kasus Pemanfaatan Portal Desa dan Sistem Mitra Desa untuk Menciptakan Kemandirian Desa dalam Gerakan Desa Membangun di Kabupaten Banyumas Provinsi Jawa Tengah pada tahun 2011-2012) - , LISA LINDAWATI, Dr. Phil. Anna Nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The village development program has so far tended to position village as an object. The Village-to-Develop Movement (Gerakan Desa Membangun/GDM) strengthens village to become the subject of development. Being a subject, village will be self-dependence. One of the strategies in establishing the village selfdependence is using new media. This study reviewed how the development communication creates the village self-dependence by utilizing new media such as Village Partnership System (Sistem Mitra Desa) and Village Portal in the Village-to-Develop Movement (Gerakan Desa Membangun). By virtue of a study case method, this study tried to describe clearly the contemporary, unique phenomenon taking place in this movement. After a series of studies, it was found out that Development Communication of this movement used the technology relevant to the focus of development and the requirement of villagers. Also, this movement considered participatory communication in promoting the community participation and capacity. With the synergy between proper technology and participatory communication, the village obtained its self-dependence as shown by the fulfillment of community requirements, the empowerment of local institution, and the village participation as the main actor in the development process. Additionally, the process of technology utilization has opened a room for social learning by taking into account the local potential and knowledge, which was then communicated to the public. It means that village can communicate itself. The findings showed that development communication by using new media in accordance with the village requirements, along with the existence of participatory communication, can create village self-dependence.